Fascin as a useful marker for cancer-associated fibroblasts in invasive lung adenocarcinoma - Yamada, Yuko; Kurata, Atsushi; Fujita, Koji; Kuroda, Masahiko (Medicine (Baltimore), 2021)
Cancer-associated fibroblasts (CAFs) have been attracting attention in recent years, but their nature has not been fully elucidated. Although CAFs have been recognized as an important therapeutic target, therapeutic agents have not been developed to date. CAFs are characterized by their high migration rate and involvement in epithelial-to-mesenchymal transition with some displaying a dendritic morphology that is reminiscent of fascin expression.The present study was designed to immunohistochemically investigate fascin expression in lung adenocarcinoma including CAFs and compare the results with existing CAF markers.We immunohistochemically investigated fascin expression in not only cancer tissue but also CAFs from 26 autopsy cases of lung adenocarcinoma. Immunohistochemistry of α-smooth muscle actin and fibroblast activation protein was also performed.Fascin-positive staining in CAFs was observed in all cases, with a strong correlation observed with existing CAF markers α-smooth muscle actin and fibroblast activation protein (P < .001). In addition, the proportion of tumor cells showing fascin-positive staining was found to correlate with its expression in CAFs (P < .05).We propose that CAFs express fascin, and that fascin may mediate crosstalk between cancer tissue and CAFs. Fascin might be a novel therapeutic target for treatments that target the cancer stroma.